ChemInform Abstract: A High Voltage Olivine Cathode for Application in Lithium‐Ion Batteries. Issue 14 (March 2016) - Di Lecce, Daniele; Brescia, Rosaria; Scarpellini, Alice; Prato, Mirko; Hassoun, Jusef
Abstract: LiFe0.25 Mn0.5 Co0.25 PO4 is prepared by solvothermal reaction of an aqueous solution of LiOH, LiH2 PO4, MnSO4, FeSO4, CoSO4, and sucrose in ethylene glycol (autoclave, 180 °C, 20 h).